Colossal Reversible Barocaloric Effects in Layered Hybrid Perovskite (C10H21NH3)2MnCl4 under Low Pressure Near Room Temperature. (12th August 2021) - Li, Junning; Barrio, María; Dunstan, David J.; Dixey, Richard; Lou, Xiaojie; Tamarit, Josep‐Lluís; Phillips, Anthony E.; Lloveras, Pol
Abstract: Barocaloric effects in a layered hybrid organic–inorganic compound, (C10 H21 NH3 )2 MnCl4, that are reversible and colossal under pressure changes below 0.1 GPa are reported. This barocaloric performance originates in a phase transition characterized by different features: A strong disordering of the organic chains, a very large volume change, a very large sensitivity of the transition temperature to pressure and a small hysteresis. The obtained values are unprecedented among solid‐state cooling materials at such low pressure changes and demonstrate that colossal effects can be obtained in compounds other than plastic crystals. The temperature‐pressure phase diagram displays a triple point indicating enantiotropy at high pressure. Abstract : 2D organic–inorganic perovskites may offer an excellent prospect as solid‐state barocaloric refrigerants, but at present they remain unexplored. Using X‐ray diffraction and calorimetry, reversible colossal barocaloric effects of 240 J K −1 kg −1 and 10 K are obtained under low pressure changes of 0.08 GPa. The dynamic disorder originating such effects has been investigated via Raman scattering.